CYP genes are duplicated in Drosophila suzukii and carry transposable elements - Berrutti, Paula D. S.; Callegari-Jacques, Sidia M.; Valente, Vera L. S.; Deprá, Maríndia (Frontiers in Ecology and Evolution, 2026)
Gene duplication and transposable element (TE) insertions are key drivers of genome evolution and have been linked to increased insecticide resistance in insects. The aim of this study was to characterize the distribution and potential impact of TEs within and near cytochrome P450 monooxygenase (CYP) genes in the invasive pest Drosophila suzukii compared with the non-pest Drosophila melanogaster. We performed in silico analyses of the CYP gene repertoire and genome architecture in D. suzukii and D. melanogaster. We identified ten duplicated CYP genes that are exclusive to D. suzukii and absent from its closely related species D. melanogaster. These duplications are enriched with TE fragments, predominantly Helitrons. Thirty-six percent of TE sequences within CYP genes and their flanking regions carry putative transcription-factor binding sites in D. suzukii, indicating a possible role in gene regulation. Building on the proposed model of Helitron-mediated exon shuffling, our findings suggest that these elements contribute to gene rearrangement, thereby potentially enhancing functional diversity. At the genome level, D. suzukii harbors a higher overall TE content than D. melanogaster, with a relative enrichment within CYP genes. The increased TE content may have enhanced genomic plasticity, thereby facilitating the species’ invasive success, rapid population growth, and ability to adapt to diverse habitats, such as native environments and agricultural fields.